Unpacking density: Translating findings into urban design variables for carbon reduction strategies - Mehaffy, Michael West; van den Dobbelsteen, Andy (A+BE | Architecture and the Built Environment, 2015)
The last chapter identified a range of factors that contribute, individually and in common, to increased GHG emissions per capita. These factors are typically associated with comparatively denser urban forms. This chapter moves beyond density to identify the more particular variables of urban form, and urban design, that can achieve the identified reductions. The chapter examines those factors and their translation into three key urban design variables.